Estrategias de marketing para la ruta de las orquídeas - Guevara Rosero, Jairo Mauricio; Leyva Vásquez, Noryuan Carlos (Tierra Infinita, 2021)
These research aim to show a marketing strategies to promote the local tourism using the natural resource of orchids, which are maintained in thoses differents places called vivarium, in addition to the preservation, also they have become in sites visited by local and international tourists. This instrument is born through the situational diagnostic that Allows to evaluate the profile of the client and identify the needs of the tourist during their stay, as well as, implement strategies to improve products and services and increase the number of tourist and strengthen tourism in the Province of Carchi.